THE SOCIOLOGY OF KNOWLEDGE PRODUCTION IN EDUCATIONAL RESEARCH: INSTITUTIONAL BARRIERS AND MANAGEMENT STRATEGIES FOR INCLUSIVE RESEARCH PRACTICES - Sumual, Tinneke Evie Meggy; Tudus, Melisa; Luma, Sartika Cendy; Luma, Sarwendah Carol; Pajow, Lidyanti Natalia; Mogonta, Sirra (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
This study explores the sociological dynamics of knowledge production in educational research, focusing on institutional barriers and management strategies for creating inclusive research practices. Utilizing a comprehensive qualitative literature review methodology, the research critically analyzes the epistemological mechanisms that shape knowledge construction in educational contexts. Through systematic data collection and critical content analysis, the study reveals three primary findings: (1) the complex knowledge regimes that structure epistemological boundaries, (2) the power dynamics in knowledge construction, and (3) transformative epistemological strategies. The research demonstrates how academic institutions perpetuate systemic exclusion through sophisticated knowledge selection mechanisms, marginalizing alternative perspectives and knowledge from peripheral communities. By employing postcolonial, critical, and liberation theory frameworks, the study exposes the hidden political dimensions of educational research knowledge production. Key recommendations include developing participatory research methods, creating dialogic spaces across diverse perspectives, and redistributing academic capital more democratically. The study advocates for a fundamental redesign of research practices that challenge existing epistemological hierarchies and promote more inclusive, socially just knowledge production in educational research.